PENGARUH PROMOSI, LOKASI, DAN PELAYANAN TERHADAP KEPUASAN PELANGGAN JASA SERVIS MOTOR (Studi Pada Servis Motor Ahass Jati Indah Karanggeneng Lamongan) - Ali Muhajir; Ratnasari Ratnasari (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2021)
This study aims to determine the effect of promotion, location and service partially on customer satisfaction in the beautiful teak Ahass. To find out the effect of promotion, location and service simultaneously on customer satisfaction in the beautiful teak Ahass. The sampling technique uses a non-probability sampling technique that is accidental sampling and the number of respondents is 100 people. The method used is quantitative descriptive. The results of multiple linear regression analysis obtained by the equation Y = 3.428 + 0.270 X1 + 0.112 X2 + 0.393 X3. The results of the partial analysis using the t test obtained t count promotion variable X1 is (4.632) with a significant level of 5% t table 1.984. Location X2 (1.995) with a significant level of 5% t table 1.984, service X3 (6.295) with a significant level of 5% t table 1.984 has a positive and significant effect on customer satisfaction. The calculation results from the F test obtained the calculated F value of 45,942 while the F table of 2.70. The results of the value of R square + 0.577 means that promotion, location, and service affect customer satisfaction by 57.7% while the remaining 42.3% is influenced by variables outside of promotion, location and service. Promotion variables (X1), location (X2), and service (X3), partially affect customer satisfaction (Y). Promotion variables (X1), location (X2), and service (X3), simultaneously affect customer satisfaction. Among the promotion variables (X1), location (X2), and service (X3) the most dominant influence was the service variable (X3), with a coefficient value of 0.393.